2000
DOI: 10.1177/070674370004500803
|View full text |Cite
|
Sign up to set email alerts
|

First-Episode Psychosis: A Comparative Review of Diagnostic Evolution and Predictive Variables in Adolescents versus Adults

Abstract: Objective: To review the diagnostic evolution andpredictive variables ofdiagnosis and outcome infirst-episode psychosis in adolescents (age 13-19 years) and adults.Method: Literature was reviewed through MEDLlNE, Psycinfo, and PubMed, and istorically, all presentations of childhood psychosis were grouped with schizophrenia, despite Kraepelin's original distinction between schizophrenia and bipolar affective disorder. With the advent of Kolvin's work (1) and the subsequent DSM-III (2), childhood schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
(225 reference statements)
0
33
0
5
Order By: Relevance
“…Some published data indicate that diagnostic stability is greater in adult patients than in adolescents at the time of first admission; the mean age of our sample was 34 years 47 . A four-year follow-up study has found that the diagnosis of schizophrenia is more stable over time than the other psychoses 48 .…”
Section: Discussionmentioning
confidence: 78%
“…Some published data indicate that diagnostic stability is greater in adult patients than in adolescents at the time of first admission; the mean age of our sample was 34 years 47 . A four-year follow-up study has found that the diagnosis of schizophrenia is more stable over time than the other psychoses 48 .…”
Section: Discussionmentioning
confidence: 78%
“…The top four diagnoses are anxiety disorders, mood disorders (depression and bipolar), disruptive behavioural disorders (including attention deficit hyperactivity disorder (ADHD), conduct disorder and oppositional defiant disorder) and pervasive developmental disorders (including autism) 30 . Accurate diagnosis of mental disorders in children depends upon differentiating the behavioural changes associated with normal childhood development and those that may be an indicator of an underlying mental illness 3,27,31 . Consequently, the rate of misdiagnosis for first‐episode mental illnesses in children is high 27,29 .…”
Section: Resultsmentioning
confidence: 99%
“…Menezes and Milovan 27 conducted a review of the literature related to first‐episode psychoses and found that females tend to have better outcomes, they exhibit higher Global Assessment Functioning scores, shorter durations of illness, fewer hospitalizations and lower risk of suicide. Gender seems to be an important element to consider in treatment approaches for young people using substances, particularly when a comorbid disorder exists.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations